El aprendizaje organizacional y sus efectos en las organizaciones actuales (2019)
This document was developed in order to demonstrate how organizational learning has generated a great impact on current organizations, that by comparing old methodologies and models with current knowledge management models. The importance of implementing strategies that address learning from a posture not only individual but also group and business was established, it was also possible to argue how the use of technology and cutting-edge tools have made these processes more effective providing efficiency in the results of organizations.